ANALISA SISTEM PENDUKUNG KEPUTUSAN (SPK) DENGAN METODE AHP DALAM MENENTUKAN KUALITAS DAY OLD CHICKEN (DOC) AYAM ARAB - Simanjuntak, Agnes Gracella Fepdiani; Suhada, Suhada; Sumarno, Sumarno; Saifullah, Saifullah (STMIK Budi Darma, 2017)
DOC is known by Day Old Chicken is a chicken one day old, the usual weight of normal average DOC Chicken in the range 35-40 gram of his recordor. Researches take a case study Arab Chicken is a descendant of chicken brkiel-silver from Belgium whose spawn ability is sufficient and generally DOC Arabian Chicken has a soft brown fur color tend to be dark, has the same shape and size both in cockerels and hens so it is very difficult to distinguish. All data collected will be implemented in a system where the system is helping to facilitate the processing of data in determining the quality of chicken DOC Arabic using AHP (Analytic Hierarchi Process). At the stage of the AHP(Analytic Hierarchi Process) Method to determine the Quality of Arab Chicken DOC begins with the process of defining the problem as a general goal in the hierarchy of powers that the Criteria and Alternatives are preferred in making pairwise comparision matrices, calculating vector values, calculating eigen vectors testing consistency and normalize the data. The use of calculations thourgh AHP (Analytic Hierarchi Process) method is faster than manual calculations so that in determining the quality of Arab Chicken DOC is much more efficient and the accuracy of the data is more assured.